Structural Model of the Relationship Between Sexual Satisfaction and Body Image Concern in Women and Men: Mediating Role of Self-esteem and Gender as Moderator in University Students - Hosein Moradi; Abbasali Allahyari; Hojjatollah Farahani (روانشناسی بالینی و شخصیت)
Introduction: Sexual satisfaction plays a crucial role in individuals' overall well-being, particularly concerning marital issues and divorce. Among the most significant factors influencing this aspect are body image concerns, self-esteem, and gender. This study investigated the simultaneous relationships among these variables within a structural model.Method: The research design of this study was correlational in nature. The target population comprised all married students attending universities in Tehran. The desired sample consisted of 200 individuals who were selected through convenience sampling and responded to the questionnaire items. To measure the research variables, we utilized the Larson Sexual Satisfaction Questionnaire (LSQQ), the Rosenberg Self-Esteem Scale (RSES), and the Body Image Concern Inventory (BICI).Results: The results of the data analysis indicate that the proposed model demonstrates a satisfactory fit following the removal of a non-significant path. The fit indices of the model indicated a good fit, with the following values: AGFI, NNFI, CFI, GFI, and NFI all exceeding 0.9. Therefore, the results of the path analysis revealed that self-esteem mediates the relationship between sexual satisfaction and body image concerns (p < 0.01).Discussion and Conclusion: Body image concerns significantly influence sexual satisfaction. However, in this context, it is essential to thoroughly consider the significant and influential role of individuals' self-esteem. As demonstrated by the modeling results in this study, there is a correlation between sexual satisfaction and body image concerns. However, when considering the role of self-esteem in this relationship, it becomes clear that body image concerns only contribute to a decrease in sexual satisfaction by affecting individuals' self-esteem.